Completeness of medication reviews provided by community pharmacists. (13th February 2014) - Kwint, H. F.; Faber, A.; Gussekloo, J.; Bouvy, M. L.
Summary What is known and objectives Little is known about the ability of community pharmacists who are inexperienced in medication review to identify drug‐related problems (DRPs). The objective of our study was to investigate the completeness of DRPs in terms of number, type and clinical relevance identified by community pharmacists when performing home medication reviews (HMRs). Methods This is a cross‐sectional study within the intervention arm of a randomized controlled trial among community‐dwelling patients (≥65 years, ≥5 drugs) in ten Dutch community pharmacies. Community pharmacists, who were inexperienced in medication review, received 2‐day training in medication review. These pharmacists interviewed patients at home about their medicines, identified potential DRPs and made recommendations in combination with medication and clinical records. Expert reviewers completed the number of potential DRPs and recommendations by reviewing all available information, including patient interview reports. Results and discussion In 155 patients, community pharmacists identified a mean of 3·6 (SD 2·8) potential DRPs per patient and expert reviewers added 6·5 (SD 3·2) DRPs. Community pharmacists formulated 2·6 (SD 2·3) recommendations per patient and reviewers added 7·5 (SD 3·3) recommendations. Community pharmacists identified a higher proportion of clinically relevant DRPs compared with expert reviewers, as assessed by DRPs with high priority [OR = 1·8 (95% CI 1·4–2·2)], DRPs associated with recommendations for drug change [OR = 1·9 (95% CI 1·5–2·3)] and implemented recommendations for drug change [OR = 2·1 (95% CI 1·6–2·7)]. What is new and conclusion This study shows that the completeness of medication reviews by inexperienced community pharmacists with limited training could be improved, although they identified a higher proportion of potentially clinically relevant DRPs compared with expert reviewers. The results suggest that community pharmacists with limited experience in medication review may need more intensive post‐graduate training.